Melatonin and Coenzyme Q10 mitigate Senescence in Human Adipose-Derived Mesenchymal Stem Cells by Restoring Mitophagy and Mitochondrial Proteostasis - Aleena Vikraman; Logeswari Ravi; Naveena Kandasamy; Anuradha Dhanasekaran (PLoS ONE, 2026)
Mitochondrial quality control is a crucial factor governing self-renewal capacity, maintenance of metabolic balance, and cellular longevity in stem cells. Impaired mitophagy significantly contributes to cellular senescence, causing accumulation of damaged mitochondria and impaired proliferative capacity of cells, leading to reduced therapeutic efficiency. This study explores mitophagy’s role in regulating senescence in human adipose-derived mesenchymal stem cells (HADMSCs) and evaluates the therapeutic potentiality of antioxidants—melatonin and coenzyme Q10 (CoQ10) targeting mitochondria. It also examines the impact of antioxidant intervention aimed at improving the fate and survival, thereby establishing a connection between metabolic reprogramming and mitophagy. Our study found that stress-induced HADMSCs have reduced Mitochondrial Membrane potential (MMP), increased ROS, and increased senescence-associated β-galactosidase activity as observed through fluorescence-based imaging and biochemical assays. It was observed that antioxidant intervention has prevented the damage caused by the stress and reduced mitochondrial ROS and lipid peroxidation and has significantly restored mitophagy markers like Parkin, NDP52, BNIP3, BNIP3L/Nix, and LC3B. Our findings suggest that antioxidants induced pharmacological stimulation of mitophagy could potentially reverse stem cell aging and prevent functional decline, thereby improving regeneration and offering new insights and perspectives on mitochondrial health for improved efficiency of stem cell transplantation, maintenance and longevity of HADMSCs.